Exosomes in osteoarthritis: Updated insights on pathogenesis, diagnosis, and treatment - Fan, Wen-Jin; Liu, Di; Pan, Lin-Yuan; Wang, Wei-Yang; Ding, Yi-Lan; Zhang, Yue-Yao; Ye, Rui-Xi; Zhou, Yang; An, Sen-Bo; Xiao, Wen-Feng (Frontiers in Cell and Developmental Biology, 2022)
Osteoarthritis (OA) has maintained a prevalent public health problem worldwide over the past decades. It is a global challenge because the specific pathogenesis of OA is unclear and there are not effective disease-modifying drugs. Exosomes are a kind of small and single-membrane vesicle secreted via the formation of endocytic vesicles and multivesicular bodies (MVBs), which eventually are released through MVBs fusing with the plasma membrane. Exosomes contain various integral surface proteins of the derived cells, intercellular proteins, DNAs, RNAs, amino acids, and metabolites. Through transferring complex constituents and promoting macrophages to generate chemokines and proinflammatory cytokines, exosomes functions in pathophysiological processes in OA, including local inflammation, cartilage calcification and degradation in osteoarthritic joints. Exosomes can also be detected in synovial fluid and plasma and continuously change with OA progression, which potentially functions as multicomponent diagnostic biomarkers for OA by exosomal miRNAs and lncRNAs. Exosomes derived from various kinds of mesenchymal stem cells and a few other kinds of cells or tissues affect angiogenesis, inflammation, and bone remodeling, presenting promising capabilities to restore OA cartilage, attenuate inflammation, and balance the formation and degeneration of cartilage matrix, indicating the therapeutic potential in OA. In combination with biocompatible and highly adhesive materials like hydrogel and cryogel, exosomes may promote cartilage tissue engineering therapy for OA. Based on numerous recent studies, we summarized the latent mechanisms and clinical value of exosomes in OA in this review.